PENCATATAN SIPIL DALAM TINJAUAN HUKUM PERDATA - Husnulwati, Sri (Solusi, 2018)
Significant events that need to be noted are the events experienced by the people who bring the consequences of the change of civil rights, as well as the birth of civil rights or the abolition of civil rights. The purpose of this research is to know how civil records are viewed from the perspective of civil law. This research is a kind of legal research which is also referred to as empirical law research. The result of this research is that the deed of civil registration has the utility or benefit from civil law point of view, namely: (1) giving legal certainty about events related to civil events such as birth, death, marriage, divorce and others, (2) authentic that determines the civil status of a person, (3) may be used for the benefit of the public service